2013
DOI: 10.1371/journal.pone.0082264
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Small Heat Shock Protein LimHSP16.45 in Arabidopsis Enhances Tolerance to Abiotic Stresses

Abstract: Small heat shock proteins (smHSPs) play important and extensive roles in plant defenses against abiotic stresses. We cloned a gene for a smHSP from the David Lily (Lilium davidii (E. H. Wilson) Raffill var. Willmottiae), which we named LimHSP16.45 based on its protein molecular weight. Its expression was induced by many kinds of abiotic stresses in both the lily and transgenic plants of Arabidopsis. Heterologous expression enhanced cell viability of the latter under high temperatures, high salt, and oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 43 publications
0
62
0
1
Order By: Relevance
“…However, only single alleles were tested, and no complementation experiments were performed. Further evidence for the stress-protective role of CI and CII sHSPs in plants has primarily involved constitutive expression or overexpression of a single sHSP in different plant species, including Arabidopsis, rice (Oryza sativa), maize (Zea mays), and carrot (Daucus carota), as well as others (Malik et al, 1999;Ahn and Zimmerman, 2006;Jiang et al, 2009;Sun et al, 2012;Zhou et al, 2012;Mu et al, 2013;Wang et al, 2015). A very restricted set of stress-resistant phenotypes has been reported for sHSP-overexpressing transgenic materials, and these studies have not provided mechanistic insight into sHSP function or distinguished differences between CI and CII sHSPs.…”
mentioning
confidence: 99%
“…However, only single alleles were tested, and no complementation experiments were performed. Further evidence for the stress-protective role of CI and CII sHSPs in plants has primarily involved constitutive expression or overexpression of a single sHSP in different plant species, including Arabidopsis, rice (Oryza sativa), maize (Zea mays), and carrot (Daucus carota), as well as others (Malik et al, 1999;Ahn and Zimmerman, 2006;Jiang et al, 2009;Sun et al, 2012;Zhou et al, 2012;Mu et al, 2013;Wang et al, 2015). A very restricted set of stress-resistant phenotypes has been reported for sHSP-overexpressing transgenic materials, and these studies have not provided mechanistic insight into sHSP function or distinguished differences between CI and CII sHSPs.…”
mentioning
confidence: 99%
“…The transcript was present in shoots as well as roots, however, the transcript abundance was higher in shoots as compared to roots. Changes in sHSPs expression are similar to those in LEA proteins at the time of dehydration and crucial developmental stages in Arabidopsis plants transformed with LimHSP16.45 (Mu et al 2013). Its strong expression in the guard cells, indicated that LimHSP16.45 probably regulated stomatal movement during times of drought.…”
Section: Expression Of Hsp In Brassica Juncea Under Drought Stressmentioning
confidence: 73%
“…HSPs accumulate in diverse plant cells in response to even a short exposure to high temperature, and are normally synthesized to maintain homeostasis of plant processes during these conditions. HSPs maintain functional conformation of other proteins and moonlight as chaperones in the assembly and transport of nascent proteins, normally as well as in response to abiotic stresses [118,[128][129][130][131]. Additionally, engineering crop plants has resulted in resistance against various abiotic stresses and industry has successfully generated drought resistant germplasm for farmers.…”
Section: Improving Abiotic Stresses Tolerance In Crop Cultivarsmentioning
confidence: 99%